‘Theorising the international relations of Asia: necessity or indulgence?’ Some reflections. - Acharya, Amitav (Pacific Review, 2017)
The study of international relations in or of Asia is no longer atheoretical, as was the case only three decades ago, when the Pacific Review was founded. But how serious are the efforts to study the international relations of Asia theoretically? Some Western scholars argue that writings on Asian International Relations (IR) are still peripheral to the major concerns and debates among IR theories such as realism, liberalism, and constructivism. The ‘indigenization’ of Asian IR theory remains limited by, among other factors, a tendency among local scholars to rely heavily on Western theories, and the close academia-officialdom nexus in the region that inhibits theoretical work. But this essay argues that Asia offers an opportunity to IR theory for broadening itself and shed its hitherto Westerncentrism, especially at a time of a ‘global’ turn in IR (global IR). Theoretical writings on Asian IR are already making a difference by exposing the limitations of mainstream IR theories in the regional context. And they have the potential to offer new and alternative concepts that are more contextually grounded and relevant for Global IR. At the same time, there remain some important conditions that must be met before theoretical writings on Asian IR can make further progress and realize their full potential.